Effects of iodine and selenium supplementation on growth, carcass characteristics and meat quality of crossbred Kacang goats - Aghwan, Zeiad Amjad Abdulrazzak (2013)
Unlike in sheep and cattle, research work in relation with the effects of trace elements such as selenium (Se) and iodine (I) on metabolism and meat quality in goats are rather limited. In most parts of the world, there are still Se and I deficiencies which justify continuous efforts to fortify compound animal feeds with Se and I for the enhancement of growth and health of goats as well as an intervention to produce Se and I enriched meat and organs for human consumption. The objective of this study was to investigate the impact of dietary supplementation of iodine, selenium and a combination of both at a level of 0.6mg/kg DM on growth performance, carcass characteristics, myosin heavy chain-slow and fast proteins distribution and meat quality of local Kacang crossbred male goats. A total of twenty four, 7 to 8 months old animals with a mean live weight of 22.00 ± 1.17 kg were randomly assigned to either one of four dietary treatments groups each consisting of 6 animals. The four dietary treatments were: T1 (control) – basal diet without supplementation; T2 – basal diet with 0.6 mg Se/kg DM; T3 – basal diet with 0.6 mg I/kg DM; T4 – basal diet with combination of 0.6 mg Se/kg DM and 0.6 mg I/kg DM. The inorganic selenium was given in the form of sodium selenite while inorganic iodine was in the form of potassium iodide. The basal diet offered was a concentrate mix based on palm kernel cake, corn and rice bran. The amount of concentrate offered was based on 1% of body weight with ad libitum amount of fresh guinea grass. After 100 days of feeding, the animals were slaughtered following which supraspinatus (SS), longissimus lumborum (LL), semitendinosus (ST) muscles were sampled from each carcass. Representative muscle samples were dissected at 3 specific periods, that is, immediately after evisceration (30 min), 24 h and 7 days post mortem to represent the unconditioned (pre-rigor), 1 day-conditioned (chilled) and 1 week-conditioned samples, respectively. The animals in T4 group indicated a higher total weight gain (p<0.05) and average daily weight gain (ADWG) (p<0.05) than the T1 and T2 animals. Significant improvement in the feed conversion ratio (FCR) was only noted in group T4 compared to the T1 (control) animals. In comparison with those of control, significant differences in carcass dressing percentage were presented by the T2, T3 and T4 animals. Results from this study indicated that serum of the animals subjected to T2, T3 and T4 were significantly higher (p<0.001) in Se and I concentrations than the control group. Furthermore, the increases (p<0.05) in total I and Se contents in the selected muscles (SS, LL and ST), liver and kidney of the supplemented goats have reflected positive response towards the dietary supplementations. Meanwhile, thyroid follicular epithelial cells height of the animals supplemented with I (T3) and combination of I and Se (T4) were significantly greater than those of control (T1) and Se supplemented (T2) groups. Besides, free triiodothyronine (FT3) of the animals supplemented with combination of I and Se (T4) was higher (p<0.05) than the animals supplemented with I (T3) alone. However, the dietary supplementation of Se, I and their combination did not affect the distribution of myosin heavy chain- slow and fast proteins in the SS, LL and ST muscles. With regard to meat quality, lower (p<0.05) drip loss was indicated by the muscles of T2 and T4 animals. The n-3 polyunsaturated fatty acids in the muscles of all supplemented groups were significantly higher than the control group. The concentrations of malondialdehyde in SS, LL and ST muscles obtained from T2 and T4 animals were significantly lower than those of T1 and T3 at day 7 post mortem. Additionally, significantly higher activities of glutathione peroxidase enzyme in serum, liver and muscles (SS, LD and ST) were also exhibited by the T2 and T4 animals. Generally, the present study demonstrated.